Capillary crystalline waterproof agent and preparation method thereof

By adding specific composition base materials and additives to the permeable crystallization waterproofing agent, the existing waterproofing agent has solved the problem of insufficient crystallinity strength and poor water pressure resistance, and has the function of automatically repairing microcracks, which improves the density and physical and chemical properties of the concrete.

CN119661112AActive Publication Date: 2025-03-21SHUIGUSHI NEW MATERIALS TECHNOLOGY (SHENZHEN) CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411753641.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-21
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

The penetrating crystal waterproofing agent with existing powder properties has problems such as insufficient crystallinity strength, poor water pressure resistance, easy to be washed and fall off on rainy days, and insufficient permeability in dry environments, resulting in powder cracking.

Method used

A permeable crystallization waterproofing agent including a base material and an additive consisting of sodium silicate, lithium silicate, copper silicate, ferrous sulfate, potassium red alum and water, and the additives include graphene slurry, sodium dodecyl sulfate, sodium toluene, anhydrous sodium citrate, sodium lauryl polyoxyethylene ether sodium sulfate, coconut oil, sodium chloride and calcium chloride.

Benefits of technology

It improves the permeability and water pressure resistance of the waterproofing agent. After encountering water, it can produce secondary crystallization at the defects of the base layer. It has the function of automatically repairing microcracks. It has strong resistance to changes in the base layer and is not easy to peel or fall off, which enhances the compactness and physical and chemical properties of the concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a capillary crystalline waterproof agent and a preparation method thereof, and relates to the technical field of concrete additives. The capillary crystalline waterproof agent comprises a base material and auxiliaries, the base material comprises sodium silicate, lithium silicate, copper silicate, ferrous sulfate, potassium bichromate and water, and the auxiliaries comprise graphene slurry, lauryl sodium sulfate, sodium toluate, anhydrous sodium citrate, lauryl alcohol polyoxyethylene ether sodium sulfate, coconut oil, sodium chloride and calcium chloride. The capillary crystalline waterproof agent is high in permeability, high in water pressure resistance and not prone to peeling and falling off.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of concrete, and in particular to a penetrating crystallization waterproofing agent and a preparation method thereof. Background Art

[0002] Concrete is prone to water seepage, cracking and frost heave, so waterproofing agents need to be added to prevent them.

[0003] Penetrating crystallization waterproofing agent can penetrate deeply into the concrete, react chemically with free alkaline substances to form crystals, effectively blocking all capillary channels and cracks inside the concrete, playing a role in waterproofing, anti-corrosion, dust-proofing, and anti-wear, protecting the concrete and internal steel bars and extending its service life.

[0004] However, the current powdery penetrating crystallization waterproofing agents have the following shortcomings: insufficient crystal strength, poor water pressure resistance, and the coating is easily washed off by rain on rainy days; in a dry environment, insufficient penetration is prone to powdering and cracking, resulting in surface peeling and falling off. Summary of the invention

[0005] The present invention is made in view of the above-mentioned problems and provides a penetrating crystallization waterproofing agent and a preparation method thereof.

[0006] The first aspect of the present invention provides a penetrating crystallization waterproofing agent, which includes a base material and an auxiliary agent, wherein the base material includes sodium silicate, lithium silicate, copper silicate, ferrous sulfate, potassium red alum and water, and the auxiliary agent includes graphene slurry, sodium dodecyl sulfate, sodium benzoate, anhydrous sodium citrate, sodium lauryl polyoxyethylene ether sulfate, coconut oil, sodium chloride and calcium chloride.

[0007] In some embodiments of the present invention, the base material includes, by weight: 30 to 40 parts of sodium silicate, 20 to 30 parts of lithium silicate, 2 to 5 parts of copper silicate, 2 to 5 parts of ferrous sulfate, 2 to 5 parts of potassium chromate and 20 to 40 parts of water.

[0008] In some embodiments of the present invention, the auxiliary agent includes, by weight, 0.5 to 1 parts of graphene slurry, 1 to 2 parts of sodium dodecyl sulfate, 10 to 20 parts of sodium benzoate, 0.1 to 0.5 parts of anhydrous sodium citrate, 0.1 to 0.5 parts of sodium lauryl polyoxyethylene ether sulfate, 15 to 25 parts of coconut oil, 3 to 8 parts of sodium chloride, and 0.5 to 1 part of calcium chloride.

[0009] In some embodiments of the present invention, the weight ratio of the base material to the auxiliary agent is 1:(0.01-0.05).

[0010] In some embodiments of the present invention, the solid content of the graphene slurry is 2 wt% to 5.0 wt%, wherein the diameter of the graphene flakes is 1 μm to 5 μm.

[0011] The second aspect of the present invention provides a method for preparing a penetrating crystallization waterproofing agent, comprising the following steps:

[0012] S1, adding sodium silicate, lithium silicate, copper silicate, ferrous sulfate and potassium chromium into water and stirring at a speed of 400-600 r / min for 10-20 min, then heating and cooling to room temperature to obtain a mixed solution A;

[0013] S2, mixing graphene slurry, sodium lauryl alcohol polyoxyethylene ether sulfate, sodium dodecyl sulfate, coconut oil, and anhydrous sodium citrate, stirring at a speed of 600-800 r / min for 5-10 min, then adding sodium benzoate, sodium chloride and calcium chloride, stirring at a speed of 200-300 r / min for 8-12 min, to obtain a mixed solution B;

[0014] S3, adding the mixed solution B to the mixed solution A, mixing and shearing, and letting it stand for 0.5 to 1 hour to obtain a penetrating crystallization waterproofing agent.

[0015] In some embodiments of the present invention, in step S1, heating includes heating to 50-60° C. and then keeping warm for 1-2 hours.

[0016] In some embodiments of the present invention, the preparation method of the graphene slurry includes: modifying graphene using a silane coupling agent containing double bonds to obtain modified graphene; adding modified graphene, fumaric acid, and 2-methylacrylamide into water, mixing and heating for reaction, then adding an initiator, a surfactant, and polyvinyl alcohol to heat for reaction, adjusting the pH to obtain a mixed material; modifying the mixed material using mercaptopropyl triethoxysilane to obtain mercapto-containing graphene; adding the mercapto-containing graphene and 2,2-diallyl bisphenol A into ethyl acetate, mixing, adding benzoin dimethyl ether to mix, reacting under ultraviolet light, washing and drying after the reaction, and adding water to ball-mill to obtain a graphene slurry.

[0017] In some embodiments of the present invention, the double bond-containing silane coupling agent includes one of γ-(methacryloyloxy)propyltrimethoxysilane, γ-(ethylenediamino)propyltrimethoxysilane, and diethylenetriaminopropyltrimethoxysilane.

[0018] In some embodiments of the present invention, the preparation of the mercapto-containing graphene includes: adding mercaptopropyltriethoxysilane to ethyl acetate, adding ethyl orthosilicate and stirring to obtain a mercapto-containing mixed material; mixing the mixed material and the mercapto-containing mixed material evenly, adjusting the pH, stirring, standing to react, centrifuging to obtain a precipitate, washing and drying to obtain the mercapto-containing graphene.

[0019] The beneficial effects that can be achieved by the present invention are:

[0020] The present invention provides a penetrating crystallization waterproofing agent. The components such as sodium silicate, lithium silicate, and copper silicate in the base material react with water to form silica gel, which fills the capillary pores of concrete. The strong oxidizing property of potassium chromium sulfate and ferrous sulfate are combined to help increase the coagulation speed, inhibit the corrosion process in concrete, and improve the durability of concrete. The addition of graphene slurry is used together with sodium chloride and calcium chloride to adjust the ionic strength of the waterproofing agent, affecting its penetration and crystallization process in concrete, which not only improves the permeability of the waterproofing agent, but also the microstructure of graphene helps to improve the durability and structural stability of concrete; coconut oil is used to improve the adhesion and flexibility of the waterproofing agent, thereby enhancing the bonding performance of concrete and other materials.

[0021] The waterproofing agent of the present invention has strong permeability and water pressure resistance, can produce secondary crystallization at base defects after encountering water, has the function of automatically repairing defects such as microcracks, has strong resistance to base changes, is not easy to peel or fall off, and can improve the density and physical and chemical properties of concrete. DETAILED DESCRIPTION

[0022] The following description is provided for those skilled in the art to fully understand the present invention, and is not intended to limit the subject matter described in the claims.

[0023] The "range" disclosed in the present invention is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present invention, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, wherein a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0024] If not otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form a new technical solution.

[0025] Unless otherwise specified, all technical features and optional technical features of the present invention can be combined with each other to form a new technical solution.

[0026] If not otherwise specified, all steps of the present invention may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0027] Concrete is prone to water seepage, cracking and frost heave, so waterproofing agents need to be added to prevent them.

[0028] Penetrating crystallization waterproofing agent can penetrate deeply into the concrete, react chemically with free alkaline substances to form crystals, effectively blocking all capillary channels and cracks inside the concrete, playing a role in waterproofing, anti-corrosion, dust-proofing, and anti-wear, protecting the concrete and internal steel bars and extending its service life.

[0029] However, the current powdery penetrating crystallization waterproofing agents have the following shortcomings: insufficient crystal strength, poor water pressure resistance, and the coating is easily washed off by rain on rainy days; in a dry environment, insufficient penetration is prone to powdering and cracking, resulting in surface peeling and falling off.

[0030] In view of this, the present invention proposes a penetrating crystallization waterproofing agent, which includes a base material and an auxiliary agent. The base material includes sodium silicate, lithium silicate, copper silicate, ferrous sulfate, potassium red alum and water, and the auxiliary agent includes graphene slurry, sodium dodecyl sulfate, sodium benzoate, anhydrous sodium citrate, sodium lauryl polyoxyethylene ether sulfate, coconut oil, sodium chloride and calcium chloride.

[0031] Penetration requires penetration pressure, which is the capillary pressure in concrete. The greater the surface tension difference between solid and liquid, the smaller the wetting angle, and the greater its ability to penetrate into the capillary. The penetration depth of crystalline active waterproof coating is related to the depth of water brought in.

[0032] At the same time, the penetration depth of the waterproofing agent is not only related to the looseness of the base layer, but also to the time the active substance solution stays on the surface of the base layer. If the base layer is loose and the active substance stays on the surface of the base layer for a long time, the penetration depth of the active material will also be deeper.

[0033] Anti-seepage pressure is one of the most important indicators to measure the waterproof effect. Under normal circumstances, the crystals produced by the active substances in the penetrating crystalline waterproof material can fully fill the defects and gaps in the concrete surface and make it a rigid waterproof layer with good anti-seepage properties.

[0034] In this solution, sodium silicate, lithium silicate, copper silicate and other ingredients in the base react with water to form silica gel, which fills the capillaries of concrete. The strong oxidizing property of potassium chromium sulfate and ferrous sulfate help to increase the coagulation speed, inhibit the corrosion process in concrete, and improve the durability of concrete. The addition of graphene slurry is used together with sodium chloride and calcium chloride to adjust the ionic strength of the waterproofing agent, affecting its penetration and crystallization process in concrete. Not only does it improve the permeability of the waterproofing agent, but the microstructure of graphene also helps to improve the durability and structural stability of the concrete; coconut oil is used to improve the adhesion and flexibility of the waterproofing agent, thereby enhancing the bonding performance of concrete with other materials.

[0035] The waterproofing agent of this scheme has strong permeability and strong resistance to water pressure. It can produce secondary crystallization at the defects of the base layer after encountering water. It has the function of automatically repairing defects such as microcracks, has strong resistance to base layer changes, is not easy to peel or fall off, and can improve the density and physical and chemical properties of concrete.

[0036] In some embodiments, the base material includes, by weight: 30 to 40 parts of sodium silicate, 20 to 30 parts of lithium silicate, 2 to 5 parts of copper silicate, 2 to 5 parts of ferrous sulfate, 2 to 5 parts of potassium chromate and 20 to 40 parts of water.

[0037] In some embodiments, the auxiliary agent includes, by weight, 0.5 to 1 parts of graphene slurry, 1 to 2 parts of sodium dodecyl sulfate, 10 to 20 parts of sodium benzoate, 0.1 to 0.5 parts of anhydrous sodium citrate, 0.1 to 0.5 parts of sodium lauryl polyoxyethylene ether sulfate, 15 to 25 parts of coconut oil, 3 to 8 parts of sodium chloride, and 0.5 to 1 part of calcium chloride.

[0038] Sodium benzoate and anhydrous sodium citrate are used as early strength agents, sodium lauryl polyoxyethylene ether sulfate is used as a surfactant, coconut oil is used as a wetting agent, and the addition of graphene slurry is used together with sodium chloride and calcium chloride to adjust the ionic strength of the waterproofing agent, affecting its penetration and crystallization process in concrete. Not only does it improve the permeability of the waterproofing agent, but the microstructure of graphene also helps to improve the durability and structural stability of the concrete.

[0039] In some embodiments, the weight ratio of the base material to the auxiliary agent is 1:(0.01-0.05). Preferably, the weight ratio of the base material to the auxiliary agent is 1:0.043.

[0040] In some embodiments, the solid content of the graphene slurry is 2wt% to 5.0wt%, wherein the flake diameter of the graphene is 1μm to 5μm. The solid content and flake diameter of the graphene slurry are conducive to uniform dispersion in the waterproofing agent, reducing agglomeration, and helping to improve the stability of the waterproofing agent under different environmental conditions, including temperature changes and humidity changes.

[0041] The second aspect of the present invention provides a method for preparing a penetrating crystallization waterproofing agent, comprising the following steps:

[0042] S1, adding sodium silicate, lithium silicate, copper silicate, ferrous sulfate and potassium chromium into water and stirring at a speed of 400-600 r / min for 10-20 min, then heating and cooling to room temperature to obtain a mixed solution A;

[0043] S2, mixing graphene slurry, sodium lauryl alcohol polyoxyethylene ether sulfate, sodium dodecyl sulfate, coconut oil, and anhydrous sodium citrate, stirring at a speed of 600-800 r / min for 5-10 min, then adding sodium benzoate, sodium chloride and calcium chloride, stirring at a speed of 200-300 r / min for 8-12 min, to obtain a mixed solution B;

[0044] S3. Add mixed solution B to the mixed solution A, put it into a high-speed homogenizing shearing machine at 2900 rpm for 30 minutes of shearing, and let it stand for 0.5 to 1 hour to obtain a penetrating crystallization waterproofing agent.

[0045] In some embodiments, in step S1, heating includes heating to 50-60°C and then keeping warm for 1-2 hours.

[0046] In some embodiments, the method for preparing the graphene slurry comprises:

[0047] Graphene is modified by using a silane coupling agent containing a double bond to obtain modified graphene;

[0048] In some embodiments, 5-10 parts by weight of graphene and 3-8 parts by weight of a double-bond silane coupling agent are added to 50-100 parts by weight of water and mixed evenly, and heated to 70-90° C. for reaction for 1-3 hours. After the reaction is completed, the precipitate is centrifuged, washed, and dried to obtain modified graphene;

[0049] Adding modified graphene, fumaric acid and 2-methylacrylamide into water, mixing and heating for reaction, then adding an initiator, a surfactant and polyvinyl alcohol, heating for reaction, adjusting the pH, and obtaining a mixed material;

[0050] 4-6 parts by weight of modified graphene, 1-3 parts by weight of fumaric acid, and 1-3 parts by weight of 2-methylacrylamide are added to 50-100 parts by weight of water and mixed evenly, heated to 50-70° C. for reaction for 5-20 minutes, then 0.05-0.2 parts by weight of an initiator, 0.1-0.5 parts by weight of a surfactant, and then 0.1-0.5 parts by weight of polyvinyl alcohol are added, the temperature is kept at 50-70° C. for reaction for 1-5 hours, and a 0.5-1 mol / l sodium hydroxide aqueous solution is used to adjust the pH to neutral to obtain a graphene-containing mixed material;

[0051] The mixed material is modified by mercaptopropyl triethoxysilane to obtain mercapto-containing graphene; the graphene-containing mixed material and the mercapto-containing mixed material are uniformly mixed, 20-25wt% ammonia water is used to adjust the pH to 8-9, the mixture is stirred at 1000-5000r / min for 30-120min, and the mixture is allowed to stand for 4-6h. After the reaction is completed, the precipitate is centrifuged, washed, and dried to obtain mercapto-containing graphene;

[0052] The mercapto-containing graphene and 2,2-diallyl bisphenol A are added to ethyl acetate and mixed, and benzoin dimethyl ether is added and mixed, and reacted under ultraviolet light. After the reaction is completed, the graphene is washed, dried, and ball-milled with water to obtain a graphene slurry.

[0053] 5-6 parts by weight of mercapto-containing graphene and 8-10 parts by weight of 2,2-diallylbisphenol A are added to 100-200 parts by weight of ethyl acetate and mixed evenly, and then 0.1-0.5 parts by weight of benzoin dimethyl ether are added and mixed evenly, and the mixture is reacted at room temperature under 365 nm ultraviolet light for 20-40 minutes. After the reaction is completed, the mixture is washed, dried, and ball-milled with water to obtain a graphene slurry.

[0054] The other components of the graphene slurry water reducer interact with each other to improve water-reducing performance, collapse retention, early strength, and slow-release performance, and are effectively dispersed. It has excellent adaptability to cement and concrete, improves cement morphology, promotes the growth of cement hydration products, makes the internal structure of cement mortar compact, and further improves the compressive and flexural strength of cement mortar.

[0055] In some embodiments, the double bond-containing silane coupling agent includes one of γ-(methacryloyloxy)propyltrimethoxysilane, γ-(ethylenediamino)propyltrimethoxysilane, and diethylenetriaminopropyltrimethoxysilane.

[0056] In some embodiments, the preparation of the mercapto-containing graphene includes: adding mercaptopropyltriethoxysilane to ethyl acetate, adding ethyl orthosilicate and stirring to obtain a mercapto-containing mixed material; mixing the mixed material and the mercapto-containing mixed material evenly, adjusting the pH, stirring, standing to react, centrifuging to obtain a precipitate, washing and drying to obtain the mercapto-containing graphene.

[0057] The prepared graphene slurry adding penetrating crystallization waterproofing agent can improve the water reduction performance, collapse retention, early strength and sustained release performance. The graphene is effectively dispersed and has excellent adaptability to cement and concrete. It also improves the cement morphology, promotes the growth of cement hydration products, makes the internal structure of cement mortar compact, and further improves the compressive and flexural strength of cement mortar. The water reducer can dissociate from the hydrolysis center, so as to maintain good fluidity of the net slurry.

[0058] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following specific embodiments are only used to explain the present invention, and are not used to limit the present invention.

[0059] Example 1

[0060] In parts by weight, 35 parts of sodium silicate, 25 parts of lithium silicate, 3 parts of copper silicate, 3 parts of ferrous sulfate, and 4 parts of potassium ruthenate were added to 30 parts of water, stirred at a speed of 500 r / min for 15 minutes, then heated to 55° C. for 1 hour, and cooled to room temperature to obtain a mixed solution A;

[0061] 5 parts of graphene and 3 parts of double-bond silane coupling agent are added to water and mixed evenly, heated to 80°C for reaction for 1 hour, and after the reaction is completed, the precipitate is centrifuged, washed, and dried to obtain modified graphene; 5 parts by weight of modified graphene, 2 parts of fumaric acid, and 1 part of 2-methyl acrylamide are added to water and mixed evenly, heated to 60°C for reaction for 10 minutes, and then 0.05-0.2 parts by weight of initiator and 0.1-0.5 parts by weight of surfactant are added, and then 0.1-0.5 parts by weight of polyvinyl alcohol are added, and the temperature is kept at 60°C for reaction for 2 hours, and the pH is adjusted to neutral with an alkaline solution to obtain a graphene-containing mixed material;

[0062] The mixed material is modified by mercaptopropyl triethoxysilane to obtain mercapto-containing graphene; the graphene-containing mixed material and the mercapto-containing mixed material are uniformly mixed, the pH value is adjusted to 9 by using an alkaline solution, the mixture is stirred at 1500 r / min for 40 minutes, and the mixture is allowed to stand for 5 hours. After the reaction is completed, the precipitate is centrifuged, washed, and dried to obtain mercapto-containing graphene;

[0063] 5 parts of mercapto-containing graphene and 10 parts of 2,2-diallyl bisphenol A were added to ethyl acetate and mixed evenly, and then 0.2 parts of benzoin dimethyl ether were added and mixed evenly, and reacted at room temperature and under 365 nm ultraviolet light for 30 minutes. After the reaction was completed, the mixture was washed, dried, and ball-milled with water to obtain a graphene slurry with a solid content of 3.0 wt%, wherein the sheet diameter of the graphene was 5 μm to obtain a graphene slurry;

[0064] 0.3 parts of graphene slurry, 0.1 parts of sodium lauryl alcohol polyoxyethylene ether sulfate, 1 part of sodium dodecyl sulfate, 20 parts of coconut oil, and 0.13 parts of anhydrous sodium citrate were mixed, and the mixture was stirred at a speed of 600 r / min for 5 min, and then 13 parts of sodium benzoate, 4.7 parts of sodium chloride and 0.6 parts of calcium chloride were added, and the mixture was stirred at a speed of 200 r / min for 10 min to obtain a mixed solution B;

[0065] Mixed solution B was added to the mixed solution A, the weight ratio of mixed solution A to mixed solution B was 1:0043, shearing was continued for 30 minutes by a high-speed homogenizing shearing machine at 2900 rpm, and the mixture was allowed to stand for 0.5 to 1 hour to obtain a penetrating crystalline waterproofing agent.

[0066] Example 2

[0067] The graphene slurry used is commercially available graphene slurry purchased from Shanghai Liwusheng New Materials Technology Development Co., Ltd., and the others are referred to Example 1.

[0068] Comparative Example 1

[0069] In Comparative Example 1, no graphene slurry was added, and the rest was as per Example 1.

[0070] Comparative Example 2

[0071] In Comparative Example 2, a commercially available penetrating crystallization waterproofing agent purchased from Jinan Qingyuyuan New Materials Co., Ltd. was added, and the rest was referred to Example 1.

[0072] Performance Test:

[0073] The penetrating crystallization waterproofing agent obtained in the measurement example and the comparative example was added to the concrete (i.e., the concrete in the blank example) in an amount of 7wt% (accounting for the total weight proportion of the cementitious material), and the performance test was carried out. The test was carried out in accordance with GB18445-2012 "Cement-based penetrating crystallization waterproofing material", JC474-2008 "Mortar, concrete waterproofing agent", JC / T 1018-2020 "Water-based penetrating inorganic waterproofing agent", GBT 8077-2023 "Concrete admixture homogeneity test method", GB / T 50082-2009 "Ordinary concrete long-term performance and durability test method standard" and GB / T 8077-2012 "Concrete admixture homogeneity test method" and the results were recorded:

[0074] Table 1: Test results of Examples 1-2 and Comparative Examples 1-2

[0075]

[0076] It can be seen from Table 1 that the performance of Example 1 is the best, especially in terms of permeability resistance, early and long-term strength development, durability and surface tension. The performance of Example 2 is also good, but slightly inferior to Example 1. The performance of Comparative Examples 1 and 2 is relatively poor, especially in terms of permeability resistance and water absorption. It is confirmed that the waterproofing agent of the present invention has strong permeability and water pressure resistance. After encountering water, it can produce secondary crystallization at the defects of the base layer, has the function of automatically repairing defects such as microcracks, has strong resistance to base layer changes, is not easy to peel or fall off, and can improve the density and physical and chemical properties of concrete.

[0077] It should be noted that the present invention is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present invention are all included in the technical scope of the present invention. In addition, without departing from the scope of the main purpose of the present invention, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present invention.

Claims

1. A penetrating crystallization waterproofing agent, characterized in that: The penetrating crystallization waterproofing agent comprises a base material and an auxiliary agent, wherein the base material comprises sodium silicate, lithium silicate, copper silicate, ferrous sulfate, potassium red alum and water, and the auxiliary agent comprises graphene slurry, sodium dodecyl sulfate, sodium benzoate, anhydrous sodium citrate, sodium lauryl polyoxyethylene ether sulfate, coconut oil, sodium chloride and calcium chloride.

2. The penetrating crystallization waterproofing agent according to claim 1, characterized in that: In parts by weight, the base material comprises: 30 to 40 parts of sodium silicate, 20 to 30 parts of lithium silicate, 2 to 5 parts of copper silicate, 2 to 5 parts of ferrous sulfate, 2 to 5 parts of potassium chromate and 20 to 40 parts of water.

3. The penetrating crystallization waterproofing agent according to claim 1, characterized in that: In parts by weight, the auxiliary agent includes 0.5 to 1 parts of graphene slurry, 1 to 2 parts of sodium dodecyl sulfate, 10 to 20 parts of sodium benzoate, 0.1 to 0.5 parts of anhydrous sodium citrate, 0.1 to 0.5 parts of sodium lauryl polyoxyethylene ether sulfate, 15 to 25 parts of coconut oil, 3 to 8 parts of sodium chloride, and 0.5 to 1 part of calcium chloride.

4. The penetrating crystallization waterproofing agent according to claim 1, characterized in that: The weight ratio of the base material to the auxiliary agent is 1:(0.01-0.05).

5. The penetrating crystallization waterproofing agent according to claim 1, characterized in that: The solid content of the graphene slurry is 2wt% to 5.0wt%, wherein the diameter of the graphene sheets is 1μm to 5μm.

6. A method for preparing a penetrating crystallization waterproofing agent, characterized in that: The following steps are involved: S1, adding sodium silicate, lithium silicate, copper silicate, ferrous sulfate and potassium chromium into water and stirring at a speed of 400-600 r / min for 10-20 min, then heating and cooling to room temperature to obtain a mixed solution A; S2, mixing graphene slurry, sodium lauryl alcohol polyoxyethylene ether sulfate, sodium dodecyl sulfate, coconut oil, and anhydrous sodium citrate, stirring at a speed of 600-800 r / min for 5-10 min, then adding sodium benzoate, sodium chloride and calcium chloride, stirring at a speed of 200-300 r / min for 8-12 min, to obtain a mixed solution B; S3, adding the mixed solution B to the mixed solution A, mixing and shearing, and letting it stand for 0.5 to 1 hour to obtain a penetrating crystallization waterproofing agent.

7. The penetrating crystallization waterproofing agent according to claim 6, characterized in that: In step S1, the heating includes heating to 50-60°C and then keeping warm for 1-2 hours.

8. The method for preparing a penetrating crystallization waterproofing agent according to claim 6, characterized in that: The preparation method of the graphene slurry comprises: Graphene is modified by using a silane coupling agent containing a double bond to obtain modified graphene; Adding modified graphene, fumaric acid and 2-methylacrylamide into water, mixing and heating for reaction, then adding an initiator, a surfactant and polyvinyl alcohol, heating for reaction, adjusting the pH, and obtaining a mixed material; The mixed material is modified by mercaptopropyltriethoxysilane to obtain mercapto-containing graphene; The mercapto-containing graphene and 2,2-diallyl bisphenol A are added to ethyl acetate and mixed, and benzoin dimethyl ether is added and mixed, and reacted under ultraviolet light. After the reaction is completed, the graphene is washed, dried, and ball-milled with water to obtain a graphene slurry.

9. The method for preparing a penetrating crystallization waterproofing agent according to claim 8, characterized in that: The double-bond-containing silane coupling agent includes one of γ-(methacryloyloxy)propyltrimethoxysilane, γ-(ethylenediamino)propyltrimethoxysilane, and diethylenetriaminopropyltrimethoxysilane.

10. The method for preparing a penetrating crystallization waterproofing agent according to claim 8, characterized in that: The preparation of the mercapto-containing graphene comprises: adding mercaptopropyl triethoxysilane to ethyl acetate, adding ethyl orthosilicate and stirring to obtain a mercapto-containing mixed material; uniformly mixing the mixed material and the mercapto-containing mixed material, adjusting pH, stirring, standing for reaction, centrifuging to obtain precipitation, washing and drying to obtain the mercapto-containing graphene.

Citation Information

Patent Citations

  • Inorganic-organic composite permeable crystallization type concrete waterproof agent

    CN105084806A

  • Permeable crystallization type concrete waterproofing agent

    CN105218152A

  • Method for preparing osmosis-resisting concrete

    CN105884319A

  • Graphene self-crystallizing waterproof activity masterbatch and preparation method

    CN107176799A

  • Waterproof agent for building leakage treatment and preparation method thereof

    CN107892544A